Character Evolution and Recircumscription of the Northern Andean Begonia Section Casparya (Begoniaceae) (2019)
Sections Casparya and Semibegoniella are some of the most species rich groups of Begonia in the North Andean region. Taken together, both sections are clearly recognizable with respect to other sections of Begonia because of their distinctive fruits that open at the back of the locules and usually have no wings but horns, however the differences between the two are less clear. The gamophyllous perianth (vs. apophyllous in Casparya) and unilamellar placenta (vs. bilamellar in Casparya) have been proposed as diagnostic characters for Semibegoniella, but this distinction has been problematic due to species of intermediate morphology, and the lack of documentation of these characters in several species. Using three chloroplast markers and nuclear internal transcribed spacers of ribosomalDNA(ITS), we present a phylogeny of the Begonia sections Casparya and Semibegoniella (Begoniaceae) and representative species of related sections. We demonstrate that both sections constitute a clade, however each one is polyphyletic, and synonymize Semibegoniella with section Casparya. Character evolution analysis reveals evidence of multiple events of convergent evolution in characters frequently used to separate Begonia sections Casparya and Semibegoniella. Additional taxonomic changes derived from this study include the designation of species status to Begonia luteyorum for Begonia brevipetala var. luteynorum, and the inclusion of Begonia raimondii as a synonym of Begonia hirta. © 2019 Copyright by the American Society of Plant Taxonomists.